Remote sensing of the impacts of construction in coastal waters on suspended particulate matter concentration – the case of the Yangtze River delta, China. Issue 9 (2nd May 2016) - Cai, Lina; Tang, Danling; Levy, Gad; Liu, Dongyan
Abstract : This study investigates the capability of high-spatial resolution Landsat Thematic Mapper (TM) data to sense and document suspended particulate matter concentration (SPMC) variability resulting from the influence of large structures in coastal waters. Two bridges, located in the coastal waters of the Yangtze River delta, are used as examples. A new SPMC inverse model, relating SPMC to TM optical properties through linear regression in the red and near-infrared bands, is developed. In total, 780 samples and 30 transects taken between 2006 and 2011 were used to compare and contrast SPMC at locations upstream and downstream of the bridges. The comparisons show: (i) within a distance of 0.3 km downstream from the bridges, SPMC mostly increased by 3–60% (8.40–176.29 mg l –1 ); (ii) when SPMC values upstream were low (<300 mg l –1 ), the increase in SPMC extended to 3.0–6.5 km downstream; (iii) under conditions of high turbidity (>400 mg l –1 ) upstream, decreases in SPMC were observed in 0.3–6.5 km downstream. The bridges influenced SPMC by blocking the transport of upstream suspended particulate matter (deposition) and through stirring of the sediments near the base of their piers (resuspension). The results can be generalized to other offshore engineering structures.